Dual-functional passivation on highly-efficient air-processed FAPbI₃ perovskite solar cells fabricated under high humidity without auxiliary equipment - Bo-Tau Liu; His-Sheng Su; I-Ru Chen; Rong-Ho Lee; Yi-Fang Su; Kai-Ting Sun; Shoaib Siddique (Applied Surface Science Advances)
Formamidinium lead triiodide (FAPbI3) perovskite has garnered significant attention due to its narrow bandgap and excellent thermal stability. However, the photo-active α-phase FAPbI3 suffers the poor structural stability, easily transforming to photo-inactive δ-phase FAPbI3 at room temperature, a process that is accelerated by the moisture. While numerous methods have been proposed to address this issue, most efforts have relied on glove-box conditions, substrate heating, or air-knife flow. To date, few studies have reported a strategy for fabricating highly efficient FAPbI3 perovskite solar cells (PSCs) under humid conditions. In this study, we are the first to demonstrate the fabrication of FAPbI3 PSCs using a one-step solution deposition method in a relative humidity of 70 % without the need for auxiliary processes or equipment, achieved through the addition of a highly volatile solvent and the incorporation of methacrylic acid (MAA) into the perovskite layer. The addition of the volatile solvent enables the fabrication of FAPbI3 perovskite in a high-moisture environment without adversely affecting the phase transformation process. The MAA incorporation not only decreases pinholes in the perovskite layer but also passivates the deep-level defects through the interaction of carboxyl groups with formamidinium cations, resulting in a low trap-state density, high charge recombination resistance, and long charge lifetime. The thermal treatment used for phase transformation of the perovskite also induces the polymerization of MAA, which further improves the long-term stability of PSCs. This dual-functional passivation approach enables PSCs to achieve high power conversion efficiency, surpassing many previously reported values for PSCs fabricated without additional processes or specialized equipment, even under highly humid conditions.